MARKAZIY OSIYO VA AMIR TEMUR: AHOLINI IJTIMOIY HIMOYA QILISH SIYOSATI - Samandarov, Sanjarbek Saidovich (INTERNATIONAL CONFERENCES, 2022)
In this article, information will be provided on measures taken by Amir Temur’s policy in Central Asia with the priority of the law and the criteria of justice in social protection of its population, ensuring their rights and interests.